The Influence of Influencer Marketing and Online Customer Review on Purchasing Decision Mediated by Brand Image : A Study on Nivea Suncare Consumers among Students of Sultan Ageng Tirtayasa University - Putri; Meutia; Nupus, Hayati (PT Larva Wijaya Penerbit, 2025)
This study aims to empirically examine the influence of influencer marketing and online customer reviews on purchase decisions of Nivea suncare products, with brand image serving as a mediating variable. A quantitative descriptive method was employed by distributing questionnaires and reviewing related literature. A total of 170 undergraduate students from Sultan Ageng Tirtayasa University (cohorts 2021–2024) were selected using purposive sampling. Data were analyzed using Structural Equation Modeling (SEM) with the assistance of SmartPLS 4 software. The findings indicate that influencer marketing has a positive and significant effect on both brand image and purchase decision. Meanwhile, online customer reviews positively influence brand image but do not directly affect purchase decisions. Furthermore, brand image is proven to have a positive and significant impact on purchase decisions and mediates the relationship between influencer marketing, online customer reviews, and purchase decisions. These results highlight the strategic importance of brand image in strengthening the effectiveness of digital marketing practices.